Governance Models for Blockchain Integrated IoT Ecosystems - Rizki Indrawan; Arista Ratih; Harry Agustian; Richard Evans (Blockchain Frontier Technology, 2026)
The rapid advancement of the Internet of Things (IoT) has led to the creation of large-scale interconnected networks of smart devices capable of autonomously collecting, processing, and exchanging data in real time across diverse application domains. While this development offers significant benefits, it also introduces critical challenges related to data security, privacy protection, interoperability, and the increasingly complex governance of distributed IoT systems. Traditional centralized governance approaches often fail to address these issues effectively due to single points of failure, limited transparency, and insufficient trust mechanisms. The integration of blockchain technology into IoT ecosystems provides a promising alternative by leveraging decentralized architecture, immutable ledgers, transparency, and tamper-resistant features that enhance accountability and trust. This study aims to identify and design an appropriate governance model for blockchain-integrated IoT systems that balances security, operational efficiency, and decentralization. The research adopts a conceptual and qualitative approach through a systematic literature analysis and the synthesis of existing governance, blockchain, and IoT frameworks to develop a structured governance model. The proposed framework defines institutional roles, policy structures, decision-making processes, and control mechanisms among participating entities. The results demonstrate that a blockchain-based governance model enhances system security, operational efficiency, and inter-organizational trust by reducing reliance on centralized authorities and improving data integrity. In addition, the use of smart contracts enables automated policy enforcement, transparent coordination, and sustainable system operations, supporting scalable and resilient governance for future blockchain IoT ecosystems.